HOT CLIMATE ON THE PHYSICAL AND MECHANICAL PROPERTIES OF CONCRETE - Rizayev Bakhodir, Islombek Akhmedov, Yusupov Shavkat, Isroiljon Umarov, Aleksandr Kazadayev, Farruh Dedaxanov (Journals Park Publishing, 2022)
Compressive and tensile strength. The hardening of concrete in a dry hot climate leads to a change in its strength compared to a similar characteristic obtained for concrete hardening under normal temperature and humidity conditions. These changes are mainly related to the physico-chemical processes occurring in the hardening concrete during which determines the regularity of the manifestation of strength characteristics. The combined variable effect of temperature, solar radiation and low relative humidity leads to a change in strength.
Keywords: cement concrete pavements, Portland cement, strength, quality destruction, reconstruction.